Toxicity Test of Catharanthus roseus Flower Extract with Brine Shrimp Lethality Test Method - Melia Sari; Chemayanti Surbakti; Tetty Noverita Khairani; Willy Novita Sari; Gabriella Septiani Nasution (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Tapak dara (Catharanthus roseus) is a plant belonging to the Apocynaceae family originating from Central America and is generally grown as an ornamental plant. The purpose of this study was to determine the percentage of mortality data and the LC50 value of tapak dara methanol extract (Catharanthus roseus) against Artemia salina Leach larvae using the Brine Shrimp Lethality Test (BSLT) method. The BSLT method used consisted of 6 concentration treatments, namely 20 ppm, 60 ppm, 100 ppm, 140 ppm, 180 ppm, and 0 ppm a negative control, each of which was repeated three times. At each concentration, 10 experimental animals of 48 hours old Artemia salina Leach larvae were used. The toxic effect of the extract was identified by the percentage of mortality of Artemia salina Leach larvae using probit analysis (LC50). The results showed the linear regression equation y = 3.0809x – 12.065. This shows that the mortality of the test animals reached 50% when the compound concentration reached 34,599 ppm. Based on the toxicity test of the methanol extract of the tapak dara flower (Catharanthus roseus) using the Brine Shrimp Lethality Test (BSLT) method, in this study it was toxic because LC50>1000 ppm so it has potential as an anticancer.